YESUS SEBAGAI GURU DITINJAU DARI PENDEKATAN MENGAJAR DAN RELEVANSINYA BAGI GURU AGAMA KATOLIK - Natalis Sukma Permana (Lembaga Penelitian STKIP Widya Yuwana, 2020)
The figure of Jesus as a teacher is clearly different from the average teacher. Jesus was recognized as a teacher not only by His disciples, but by many who heard His teachings. Jesus is called the Teacher because Jesus' teacher training is based on